Eating disorder and its relationship with psychological distress in the Covid-19 pandemic in Turkey - Demirci, Onur Okan (Progress in Nutrition, 2023)
Background and aim: With the lockdown, panic buying, and stress in the COVID-19 pandemic, people have had a complex and problematic relationship with eating. We aimed to investigate pandemic-related stressful life events and the relationship between eating disorders and psychological distress in students continuing online education during the COVID 19 pandemic.Methods: This cross-sectional study included 770 students. Pandemic-related distress screening questionnaire (P- SLESQ), The Depression Anxiety Stress Scales-21 (DASS-21), and The Eating Disorder Examination Questionnaire (EDE-Q) were used for assessment.Results: Of the 770 participants, 593 (77.0%) were female, 741 (96.2%) were single. 5.6% of the participants had eating disorders, according to the EDE-Q cut-off score. Females reported more frequent disordered eating behaviors or cognitions than males (p